2021
DOI: 10.3310/hta25110
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative intravenous iron for anaemia in elective major open abdominal surgery: the PREVENTT RCT

Abstract: Background Anaemia affects 30–50% of patients before they undergo major surgery. Preoperative anaemia is associated with increased need for blood transfusion, postoperative complications and worse patient outcomes after surgery. International guidelines support the use of intravenous iron to correct anaemia in patients before surgery. However, the use of preoperative intravenous iron for patient benefit has not been assessed in the setting of a formal clinical trial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
(91 reference statements)
0
12
0
Order By: Relevance
“…However, how to treat preoperative anaemia was still controversial to a certain extent [6]. International guidelines support the use of intravenous iron to correct anaemia in patients before surgery, but a recent RCT showed no bene t from giving intravenous iron before the operation [31]. So more studies are needed to make a appropriate strategy towards preoperative anaemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, how to treat preoperative anaemia was still controversial to a certain extent [6]. International guidelines support the use of intravenous iron to correct anaemia in patients before surgery, but a recent RCT showed no bene t from giving intravenous iron before the operation [31]. So more studies are needed to make a appropriate strategy towards preoperative anaemia.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27][28] In colorectal ERAS ® pathways, iron supplementation is recommended; 29 however, the balance of trial evidence in mixed surgical populations has not shown clinically significant reductions in allogeneic blood transfusion in patients receiving preoperative iron therapy. 30,31 Caution is advised in translating certain anemia therapies to open aortic operations amid presence of US Food and Drug Administration (FDA) limitations of use of erythropoietin-stimulating agents in patients undergoing cardiac or vascular surgery, and an adverse event profile that includes thrombotic events. 32 Recommendation: Evaluate the cause of and treat chronic preoperative anemia.…”
Section: A Anemia Screeningmentioning
confidence: 99%
“…Pre-operative anemia is a common problem and can impact as much as 30% to 50% of patients presenting for surgery. 1,2 The WHO defines anemia as a hemoglobin level of less than 130 mg/mL in men and 120 mg/mL in non-pregnant women. 1 It is estimated that approximately 3% of Canadians have anemia and is most prevalent for people age 65 to 79.…”
Section: Context and Policy Issuesmentioning
confidence: 99%
“…1 This can be detrimental during surgery where blood loss may be high and may result in peri-operative blood transfusions and adverse post-operative outcomes such as inpatient complications, delayed hospital discharge, or mortality. 1,2 A 2015 National Institute for Health and Care Excellence (NICE) guideline recommends that oral iron supplementation should be the first-line treatment option for patients with anemia undergoing surgery. 2,4 Oral iron supplementation is common and inexpensive, and can be an effective method of iron supplementation; however, oral iron can be poorly absorbed by the body and compliance with oral iron treatment is often low with only 20% to 40% of patients completing a full course of treatment.…”
Section: Context and Policy Issuesmentioning
confidence: 99%